PENGARUH KARAKTERISTIK PENERIMA MANFAAT, TERPAAN MEDIA, DAN PERAN PENDAMPING TERHADAP KEBERDAYAAN MASYARAKAT DALAM PROGRAM CSR PERUSAHAAN - Lita Amalia; Dwi Retno Hapsari; Kris Harini Matindas (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aimed to analyze the influence of beneficiary characteristics, media exposure, and the role of facilitators on community empowerment in a corporate social responsibility (CSR) program. The research was conducted in the Internet Desa Digital program implemented by PT Tirta Investama in Ciherang Village, Caringin District, Bogor Regency. This CSR initiative focuses on improving digital access, digital literacy, and community economic empowerment through internet-based activities in rural areas. A survey method was employed to collect data from community members who benefited from the program. Data were obtained through structured questionnaires distributed to respondents and were analyzed using descriptive statistics and multiple linear regression analysis to examine the influence of the independent variables on community empowerment. The findings show that media exposure and the role of facilitators significantly influence community empowerment, while beneficiary characteristics do not have a significant effect. Media exposure plays an important role in increasing public awareness and understanding of the program through the frequency, intensity, and duration of information dissemination. Meanwhile, the role of facilitators functions as a bridge between the company and the community by providing training, technical assistance, and participatory communication that support the community in utilizing digital technology. The Internet Desa Digital program contributes to strengthening digital literacy, improving economic opportunities, and enhancing community participation in village development. Keywords: corporate social responsibility, media exposure, facilitators, community empowerment, digital village.